Monitores sob ataque: do Alagoas em Humaitá ao Pernambuco em Porto Esperança, a dura arte de aprender lições - Fernando Ribas De Martini (Navigator)
This article is about the combat experiences of two monitors built in Brazil at different times, and the histori-cal evidence of the use (or not) of these lessons in later designs for the Brazillian Navy. One of them, Alago-as, stood out in the Passage of Humaitá in 1868 as it faced the Humaitá fortress cannons, and its design took advantage of the experience gained with ships in service at the War of the Triple Alliance (1864- 1870), ac-cording to sources. Another was Pernambuco, incorporated in 1910, whose delayed construction apparently incorporated lessons from preceding ships. However, when entering combat in the Constitutionalist Revolu-tion of 1932, it suffered its greatest threat by a weapon that did not exist at the time of its project: the air-plane. Would there still be historical lessons, for now and the future, from Humaitá (1868) and Porto Espe-rança (1932)? We believe so.